2009
DOI: 10.1002/ijc.24124
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of colorectal cancer: A systematic review and meta‐analysis of prospective cohort studies

Abstract: An inverse association between coffee consumption and the risk of colorectal cancer has been found in several case-control studies, but such an association was not consistent in prospective cohort studies. We conducted a systematic meta-analysis of prospective cohort studies on coffee consumption and colorectal cancer published up to June 2008. We combined relative risks (RR) for colorectal cancer comparing high vs. low categories of coffee consumption using random-effects models. We identified 12 eligible coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 50 publications
8
87
0
2
Order By: Relevance
“…However, there was a slight suggestion of an inverse association between coffee consumption and colorectal cancer (RR 5 0?94, 95 % CI 0?88, 1?01; P for heterogeneity 5 0?85; I 2 5 0 %; . For duration of follow-up, we applied 10 years of follow-up as a cut-off because the mean of follow-up time for all sixteen cohort studies was roughly 10?5 years (6) and there were nine and seven studies whose follow-up periods were over and less than 10 years, respectively. Results of analyses in stratum of follow-up period indicated that studies with shorter followup time (,10 years) tended to show marginally inverse relationships between coffee intake and the risks of colorectal (RR 5 0?92, 95 % CI 0?85, 1?01) and colon caner (RR 5 0?90, 95 % CI 0?81, 1?00; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was a slight suggestion of an inverse association between coffee consumption and colorectal cancer (RR 5 0?94, 95 % CI 0?88, 1?01; P for heterogeneity 5 0?85; I 2 5 0 %; . For duration of follow-up, we applied 10 years of follow-up as a cut-off because the mean of follow-up time for all sixteen cohort studies was roughly 10?5 years (6) and there were nine and seven studies whose follow-up periods were over and less than 10 years, respectively. Results of analyses in stratum of follow-up period indicated that studies with shorter followup time (,10 years) tended to show marginally inverse relationships between coffee intake and the risks of colorectal (RR 5 0?92, 95 % CI 0?85, 1?01) and colon caner (RR 5 0?90, 95 % CI 0?81, 1?00; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was a slight suggestion of an inverse association between coffee consumption and colon cancer in women (RR 5 0?79; 95 % CI 0?60, 1?04) (6) . Our findings confirmed these previous results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple epidemiological studies have demonstrated an inverse association between coffee consumption and risk of colorectal cancer (4)(5)(6). However, the molecular basis of this effect remains to be fully understood (7).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1), while a borderline protective effect was also shown for colon cancer. This effect was stronger in women (RRZ0.79) than in men (RRZ1.00), particularly in Japanese populations (RRZ0.62), although a plausible explanation for this sex difference deserves further investigation (Je et al 2009). A recently large-scale prospective study in the US reported a null association for total cancer mortality (Freedman et al 2012), which suggests that the effect of coffee varies by cancer site, likely depending on whether it is associated with insulin resistance or not.…”
Section: Physical Activity and Cancer Riskmentioning
confidence: 95%